Assessment of the effect of nebivolol and сarvedilol on the functional state of patients with diastolic chronic heart failure - Vitalii G. Tregubov (Concilium Medicum, 2021)
Aim. To determine the effect of combined therapy with nebivolol or carvedilol on the functional state of patients with diastolic chronic heart failure (CHF).